The Effect of Acupuncture and Acupressure Therapy Against a Decline in The Level of Pain in Lower Limb Pain in Dukuh Duwetan - Imrok Atus Sholihah (PLACENTUM: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
Background: The Lower Limb is the body prone to pain and injuries due to prop up the overall weight. Acupuncture is an eastern medicine with stabbing needles on the specific surface area of the body that can cause analgesic effects. Acupressure massage therapy development emphasizes acupuncture points that increase the saturation of oxygen and cause muscle relaxation effects. Our study aimed to identify the influence of acupuncture and acupressure therapy against a decline in the lower limb pain sufferers' pain level. Subject and method: The study was conducted in February-March In Dukuh Duwetan, Village Jumantono, district Ngunut, Karanganyar Regency. The sample of the research taken is 30 farmers, both men, and women, aged 30-50 years have lower limb pain complained during and after work. This research is a pre-experimental design with One Group pretest-posttest with a 30 community Dukuh Duwetan meets the criteria of inclusion. The data collected is the primary data with the recording and assessment of the results of the action. Statistical tests using univariate analysis and bivariate analysis using Wilcoxon. Result: There is a decreasing scale of pain in lower limb pain sufferers community Dukuh Duwetan with the value of the Wilcoxon test p = 0.00 < 0.05. Conclusion: The presence of acupuncture and acupressure therapy were influence against downturn lower limb pain.